“What I do not see and others see in me”: mutual aid for suicide recovery in Colombia - Felipe Agudelo-Hernández; Lina Valeria Cuadrado; Andrés Camilo Delgado-Reyes (International Journal of Qualitative Studies on Health & Well-Being)
Purpose In response to the rise in suicidal behaviour and the strategies to address it, community actions represent a comprehensive approach to the factors influencing this situation. The aim of this study was to analyse the influence of mutual support on the recovery of individuals who experienced suicidal behaviour and attended community mental health groups. Methods A qualitative study was conducted in 2023. Focus groups were used as a data collection technique, followed by thematic analysis. Participants were selected based on convenience from mutual support groups registered with the Ministry of Health of Colombia. Results Two main themes were identified in the thematic analysis. The first theme, “Own Reasons Through Others,” was composed of categories such as “What Others See in Me” and “The Importance of Being in the Same Boat.” The second theme was titled “The Community as a Space for Suicide Prevention,” with categories including “Human Rights for Recovery” and “What We Can Achieve Together.” Conclusions Pluralism, understood as the integration of diverse perspectives, is crucial for addressing complex phenomena such as mental health and community interventions. The study demonstrates how mutual aid groups and their members can generate collective and policy actions effective for managing suicidal behaviour.